Gene expression changes in ducklings exposed in ovo to emerging and legacy per-/poly-fluoroalkyl substances - Brand, Anne-Fleur; Peterson, Silje; Günzel, Louisa M. S.; Yap, Kang Nian; Ciesielski, Tomasz M.; Arzel, Céline; Jaspers, Veerle L. B. (Elsevier, 2026)
This study investigated the effects of two emerging per- and polyfluoroalkyl substances (PFAS), perfluorododecane sulfonic acid (PFDoDS) and perfluoro-4-ethylcyclohexane sulfonic acid (PFECHS), alongside legacy perfluorooctanesulfonic acid (PFOS) on mallard ducklings (Anas platyrhynchos) exposed in ovo. These PFAS compounds were selected based on their detection in a declining sea duck species and concerns over their endocrine disruption potential. Farmed mallard eggs were injected with 80 ng/g of PFDoDS, PFECHS, or PFOS, simulating maternal transfer to the egg and reflecting concentrations at the upper end of those reported in wild bird eggs. Gene expression was assessed in the liver, heart, and bursa of Fabricius. In the liver, messenger RNA (mRNA) and small RNA sequencing revealed sex-specific changes in genes related to metabolism and immune function, particularly antiviral responses, in PFECHS- and PFDoDS-exposed ducklings. Notably, there was overlap between male PFECHS- and PFOS-exposed groups. In the heart, quantitative polymerase chain reaction (qPCR) analyses of mRNAs and microRNAs associated with stress, inflammation, and development showed no differences, though trends included altered expression of genes involved in oxidative and cellular stress responses across treatments. In the bursa of Fabricius, qPCR of immune-related mRNAs revealed upward trends in innate immune gene expression across all exposure groups, also consistent with antiviral immune activation, suggesting shared transcriptional effects among these sulfonated PFAS. These findings demonstrate that emerging PFAS exposure alters gene regulation related to key physiological pathways, with responses differing by sex and tissue type. Our results underscore the complexity of PFAS-induced immunomodulation and highlight potential developmental risks of maternal PFAS transfer in wild avian species.